Pelatihan Pemahaman Ekowisata : Daya Tampung Destinasi Wisata Dan Konservasi Lingkungan di Komunitas Mahasiswa Pariwisata - Anggara, Bagas; Hardyanti, Hardyanti; Cahyani, Arie; Lestari, Ayu Ambang; Elthia, Memy Wardani (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2024)
Training on ecotourism and environmental conservation for students of the Sharia Tourism Study Program at UIN Mataram is an initiative based on the profound need for understanding ecotourism and the importance of environmental preservation in the tourism industry. This research is motivated by the rapid development of tourism in Lombok Island, which has not been accompanied by awareness of environmental preservation and sustainable values. The training aims to provide students with a deeper understanding of the concepts of ecotourism, environmental conservation, and carrying capacity of tourist destinations. The implementation method of the training includes coordination with students as organizers, literature review to delve into the concepts of ecotourism and environmental conservation, and conducting training at the Faculty of Economics and Business at UIN Mataram. The results and discussions show an increase in understanding and awareness among students about the importance of environmental conservation in the tourism industry. They are equipped with practical skills in managing sustainable tourist destinations. This training has successfully had a positive impact on enhancing the understanding, awareness, and skills of UIN Mataram Tourism students in the field of ecotourism, environmental carrying capacity, and conservation. Through this training, it is hoped that students can become agents of change who bring positive impacts to the environment and surrounding communities through sustainable and responsible tourism practices.